Applied music studio teachers in higher education: evidence of learner-centred teaching. (27th May 2019) - Daniel, Ryan; Parkes, Kelly A.
ABSTRACT: One of the key goals within the global higher education sector is to continue to improve current practice in learning and teaching. Associated with this push is accountability or compliance, in terms of institutional leaders and teaching staff being able to evidence the ways in which student learning outcomes are achieved. A current area of focus in higher education is the concept of learner-centred teaching, where the student is expected to contribute more to the teaching and learning transactions. Amidst this context, this paper focuses on the applied studio teaching model in music, also known as the one-to-one lesson. Involving 54 current practitioners across four countries, survey findings reveal that numerous teachers have had no formal training in pedagogy and thus describe their teaching in different ways to those that have had training. Implications for professional development of applied studio teachers are discussed and suggestions for further research are also presented.